Changes in IgA-targeted microbiota following fecal transplantation for recurrent Clostridioides difficile infection. (1st January 2021) - Huus, Kelsey E; Frankowski, Marcin; Pučić-Baković, Maja; Vučković, Frano; Lauc, Gordan; Mullish, Benjamin H; Marchesi, Julian R; Monaghan, Tanya M; Kao, Dina; Finlay, B. Brett
ABSTRACT: Secretory immunoglobulin A (IgA) interacts with intestinal microbiota and promotes mucosal homeostasis. IgA-bacteria interactions are altered during inflammatory diseases, but how these interactions are shaped by bacterial, host, and environmental factors remains unclear. In this study, we utilized IgA-SEQ to profile IgA-bound fecal bacteria in 48 recurrent Clostridioides difficile patients before and after successful fecal microbiota transplantation (FMT) to gain further insight. Prior to FMT, Escherichia coli was the most highly IgA-targeted taxon; following restoration of the microbiota by FMT, highly IgA-targeted taxa included multiple Firmicutes species. Post-FMT IgA-targeting was unaffected by the route of FMT delivery (colonoscopy versus capsule), suggesting that both methods lead to the establishment of healthy immune–bacterial interactions in the gut. Interestingly, IgA-targeting in FMT recipients closely resembled the IgA-targeting patterns of the donors, and fecal donor identity was significantly associated with IgA-targeting of the recipient microbiota. These data support the concept that intrinsic bacterial properties drive IgA recognition across genetically distinct human hosts. Together, this study suggests that IgA-bacterial interactions are reestablished in human FMT recipients to resemble that of the healthy fecal donor.